ENHANCING HEALTHCARE SYSTEM MANAGEMENT: CHALLENGES AND STRATEGIC SOLUTIONS (World Bulletin of Public Health, 2024)
The problem of medical management is one of the most difficult and urgent tasks in modern healthcare. Effective management of medical institutions requires coordination of many factors, including the organization of medical care, resource management, personnel policy, as well as ensuring the quality and safety of medical services. To effectively address these issues, a comprehensive strategy is necessary. This includes implementing advanced information systems, enhancing the professional skills of management staff, and optimizing both funding and resource allocation. Only with a systematic and targeted approach is it possible to achieve a high level of medical care and sustainable development of the healthcare system. Optimization of medical management with the help of modern technologies can significantly improve the efficiency of medical institutions, improve the quality of patient care, and reduce operating costs. The introduction of electronic medical records, artificial intelligence (AI), telemedicine, and automation of administrative processes create the basis for sustainable and innovative development of healthcare. This article discusses the problems associated with management in the field of healthcare. Various factors influencing the successful management of medical institutions, as well as the role of nurses in medical practice, are highlighted. In the context of the tasks set out in the "Concept for the development of the healthcare system in the Republic of Uzbekistan 2022-2026", the solution of these problems becomes especially relevant.
Keywords: healthcare; medical management; AI in medicine